A comparative study for bandwidth on demand using ONOS reactive and intent forwarding - Fathul Arif Kamarudin; Megat Norulazmi Megat Mohamed Noor; Fuead Ali (Institute of Advanced Engineering and Science, 2020)
Telco operators need to tailor their networks to be agile, efficient and able manage the operational cost at moderate level. Furthermore, the norm of network volatility practiced by many enterprises open to a new challenge in managing an increasing traffic over the same WAN. For an enterprise, turning toward Bandwidth-on-Demand (BoD) approach promises to deliver extra network capacity when in demand without the complexity of running separate network. However, they need to manually transform these high-level policies into low-level configuration command and thus error-prone. This study was to address the effects of SDN (software-defined network) on the BoD performance towards the differences between the reactive and intent forwarding based on the assessment matrix. The testbed was performed under Mininet simulator which interacted with ONOS (Open Network Operating System). Mesh type topology with a predetermine parameter matrix was used using random topology generator. The expected outcome from this research was to show the effect on the BoD performance under two type of forwarding; reactive and intent based on the assessment matrix. This report contributed towards determining the effectiveness of SDN architecture on BoD performance and to improve future benchmarking on SDN-BoD testbed.